PREVALENCE OF Theileria annulata AND THE FIRST REPORT OF Theileria sinensis IN CATTLE FROM ERBIL PROVINCE, IRAQ - Wahab, Musa A; Aziz, Khalid J (Science Journal of University of Zakho, 2026)
Bovine theileriosis is a significant tick-borne protozoan disease of cattle, primarily caused by species of the genus Theileria. This study investigated the prevalence of bovine theileriosis in cattle using both microscopic examination and conventional PCR (c-PCR). Microscopic analysis of Giemsa-stained blood smears identified an infection rate of 51/236 (21.6%), while c-PCR revealed a significantly higher prevalence of 106/236 (44.9%). Theileria species were characterized morphologically and confirmed via molecular methods. PCR analysis identified Theileria annulata and Theileria sinensis as the causative agents, with T. annulata showing the highest rate of single infections 89/106 (84%) compared to T. sinensis 17/106 (16%). Mixed infections were detected in 13/106 (12.3%) of cases. Age, sex, breed, housing conditions, acaricide use, and tick infestation were identified as key risk factors influencing infection rates. Management and tick-related factors significantly influenced Theileria prevalence, with higher infection rates observed in cattle with tick infestation 54/102 (52.9%), irregular or no acaricide use 58/115 (50.4%) and 27/47 (58.7%) respectively, non-cemented floors 72/125 (57.6%), and tick presence in barns 64/127 (50.4%). Phylogenetic analysis demonstrated genetic similarities between the identified T. annulata and T. sinensis sequences and strains reported from other geographical regions. Notably, this study provides the first report of T. sinensis in Iraq, highlighting its emergence and underscoring the need for enhanced surveillance and control measures against Theileria infections in the country. The high prevalence of the disease underscores the urgent need for enhanced surveillance, effective tick control measures, and the implementation of integrated strategies to mitigate the impact of bovine theileriosis on cattle health and productivity.